Association of a BACE1 Gene Polymorphism with Parkinson’s Disease in a Norwegian Population - Johannes Lange; Kristin Aaser Lunde; Camilla Sletten; Simon Geir Møller; Ole-Bjørn Tysnes; Guido Alves; Jan Petter Larsen; Jodi Maple-Grødem (Parkinson's Disease)
Background. Parkinson’s disease (PD) and Alzheimer’s disease (AD) share pathological features, including amyloid-beta pathology. Amyloid-beta peptide is generated by sequential proteolysis of amyloid precursor protein (APP), and genetic variations in the processing pathway genes have been found to increase the risk of AD; however, the contribution in PD is unknown. Methods. The aim of this study was to investigate whether candidate polymorphisms in five genes (ADAM10, BACE1, BACE2, PSEN2, and CLU) involved in the APP processing pathway affect PD risk in a population-based cohort of patients with incident PD and control subjects from the Norwegian ParkWest study. Results. We found an association of rs638405 in BACE1 with increased risk of PD, thus providing a novel link, at the genetic level, between amyloid-beta pathology and PD.